Removal of Hexavalent Chromium from Aqueous Solutions Using Magnetic Nanoparticles Coated with Alumina and Modified by Cetyl Trimethyl Ammonium Bromide - Mohammad Malakootian; Asghar Askarpuor; Najmeh Amirmahani; Zahra Nasiri; Alireza Nasiri (Shahid Sadoughi University of Medical Sciences, 2015)
Introduction: The development of an effective method regarding chromium removal from the environment is of great importance. Therefore, the present study aimed to examiner magnetic nanoparticles coated with alumina modified by Cetyl Trimethyl Ammonium Bromide (CTAB) in the removal of Cr6+ through magnetic solid phase extraction method. Materials & Methods: At first, iron oxide nanoparticles were synthesized, coated with alumina, modified with CTAB and characterized with suitable instruments. The factors affecting the process of chromium removal were investigated, including the concentration of CTAB, the pH, the amount of nanoparticles, the sample volume, a proper eluent, the adsorption and desorption time, and the effect of interfering ions. Moreover, the chromium concentration was determined by flame atomic absorption spectrometric (FAAS) technique. The adsorption isotherm, adsorption capacity, and recoverability of the adsorbent were further examined. Results: The modified magnetic nanoparticles were demonstrated to be homogeneous, spherical, with a size lower than 20 nanometer having a magnetic property. The optimal conditions for chromium removal entailed 7*10-6 mol/L concentration of CTAB, pH range of 6-8, 0.1 g of the nanoparticles, 10 mL volume of the chromium sample (5 &mug mL-1), nitric acid 2 M as a suitable eluent, 15 minutes of adsorption and desorption, and no interference of interfering ions in the process of chromium separation. The process efficiency under optimal conditions was determined to be over 95%, which this process followed the Langmuir adsorption isotherm. The adsorption capacity proved to be 23.8 mg/g. Reusing after four times of adsorbent recovering was effective in the chromium removal (80%). The method accuracy for five measurement times was 4.155% and the method’s LOD was 0.081 mg/L. Conclusion: The method enjoys the benefits of convenient preparation of the adsorbent, high selectivity, high accuracy, short process time, and high-efficiency in chromium removal from aquatic environments, lending itself to be used in the real samples.